Researching building equation of natural convection air flow velocity in 5 x 6 m2 (3,5 tons/batch) tobacco dryer chamber - Hay, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 20 No 2, 2004)
Researching-building equation of natural convection air flow velocity in 5  X  6 m2 (3,5 tons) tobacco dryer chambers. One of the factors influencing in the quality of dried tobacco in handicraft tobacco dryer is velocity of air flow through the layer of leaf tobacco. Based on theory, the equation is pointed out and based on experiments, coefficients are confirmed. Finally, the equation is completed so that it is used for the 5 x 6 m2 (3,5 tons) tobacco dryer. Mass of air entering the dryer chamber influences greatly on escaping humidity and quality of leaf tobacco. They depend on surface of inlet and outlet, resistance of tobacco leaves in the tobacco dryer chamber, and the difference of temperature inside and outside dryer chamber. Therefore, an equation of velocity of the natural convection air flow through the leaf tobacco layer is established for designing dryer.